Signal Lights-Based Light Vehicle Safe Movement on Underground Mine Ramps - Laud Christian Ainoo; Erwin Normanyo (JURNAL NASIONAL TEKNIK ELEKTRO, 2022)
The safe movement of Light Vehicles (LVs) is jeopardised on underground mine ramps due to the single lane nature of ramp and the use of ramp by Heavy Vehicles (HVs). Two-way traffic flow dynamics in single-lane underground mine haulage ramps do affect productivity of ramp in times of ore transportation from underground to the surface for processing. In this research, we made use of traffic signal lights, Radio Frequency (RF) Transmitters (Tx) and Receivers (Rx) and a traffic signal lights module to safeguard LV motion on underground ramp. Simulation outcomes confirm safe movement of LV in the midst of HV and other LV on the haulage ramp. This development assures of safety of LV and stands to minimise the incidents occurrences rate in mine ramp haulage systems.